SECURITIZATION OF AUSTRALIA'S MIGRATION ISSUES DURING SCOTT MORRISON'S LEADERSHIP ERA - Sabrina, Ayu; Susiatiningsih, Hermini; Wahyudi, Fendy Eko (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2022)
In the last two decades, the Australian Government has intensified the practice of securitizing migration issues. The difference is that the pre-Scott Morrison migration securitization program was more focused on handling cases of Illegal Maritime Arrivals, while the core of Scott Morrison's migration program was to reduce the pressure on the immigrant population. Through the discourse of Planning for Australia's Future Population, Scott Morrison cut the quota of permanent immigrants from 190,000 to 160,000 people. Scott Morrison also implemented immigration transfer policies and migration reforms. Therefore, this study focuses on analyzing the process of framing the issue of Australian immigrants under the leadership of Scott Morrison. This research uses securitization theory and qualitative methods, particularly process-tracing. As a result, this research found that Scott Morrison, as the securitization actor, intentionally created a speech act and convinced the public that the referent object, namely Australia's national security, was in a threatening situation due to the surge in the immigrant population. Functional actors, including parliament, media, and epistemic groups, reinforced Scott Morrison's speech acts.